2020
DOI: 10.1021/acsapm.0c00443
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Stable Sulfonated Polytriazoles Containing Trifluoromethyl and Phosphine Oxide Moieties for Proton Exchange Membranes

Abstract: Polytriazoles are considered as an excellent high-performance polymer due to their outstanding set of properties. The current investigation reports the synthesis of a phosphorus-containing fluorinated diazide monomer, that is, bis[4-(4′-azidophenoxy)-3-trifluoromethyl phenyl] phenylphosphine oxide (PFAZ) and utilization of this compound to synthesize a set of trifluoromethyl groups and phosphine oxide containing sulfonated polytriazoles (PTPFBSH-XX). The copolymers with a different level of sulfonation (-XX = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(78 citation statements)
references
References 63 publications
3
75
0
Order By: Relevance
“…All other chemicals were used without additional purification. The compounds 4,4′-(propane-2,2′-diyl)­bis­((prop-2-ynyloxy)­benzene) (bisphenol-based dialkyne (BPALK)) and 1,1-bis-(4-aminophenyl)-1-(6-oxido-6 H -dibenz⟨ c , e ⟩⟨1,2⟩oxaphosphorin-6-yl) ethane (DPA) were prepared according to reported procedures. , …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All other chemicals were used without additional purification. The compounds 4,4′-(propane-2,2′-diyl)­bis­((prop-2-ynyloxy)­benzene) (bisphenol-based dialkyne (BPALK)) and 1,1-bis-(4-aminophenyl)-1-(6-oxido-6 H -dibenz⟨ c , e ⟩⟨1,2⟩oxaphosphorin-6-yl) ethane (DPA) were prepared according to reported procedures. , …”
Section: Methodsmentioning
confidence: 99%
“…In light of such interesting chemistry, some sulfonated copolytriazoles have been synthesized effectively by CuAAC-type click polymerizations of terminal diazides and dialkynes, and their PEM-related studies have been reported. The aromatic nature of the triazole ring provided oxidative and hydrolytic stability, and the basic nitrogen sites functioned as proton charge carriers by accepting protons from the sulfonic acid part. , Moreover, the sulfonated copolytriazoles with the phosphine oxide moiety showed encouraging results in dimensional stability, water management, proton conductivity, and oxidative stability compared to numerous other polymers. , In these types of highly conductive polytriazoles, a unique kind of proton-conducting channels was created by hydrogen bond formation among the sulfonic acid (−SO 3 H), phosphine oxide (−PO), and triazole rings. , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various membrane materials have been applied to PEMs [20, 44,54]. Thermally stable polymers with -SO 3 H groups in the main and side chains have been widely employed as PEMs because of their high proton conductivities and easy modification [20, [55][56][57]. Sulfonated polymers are generally amphiphilic.…”
Section: Materials For High-temperature Pemsmentioning
confidence: 99%